Physicochemical evaluation of hydrogen peroxide bleaching gels containing titanium dioxide catalytic agent, and their influence on dental color change associated with violet LED - Carlos, Natália Russo; Basting, Rosanna Tarkany; Amaral, Flávia Lucisano Botelho do; França, Fabiana Mantovani Gomes; Turssi, Cecilia Pedroso; Kantovitz, Kamila Rosamilia; Bronze-Uhle, Erika Soares [UNESP]; Lisboa Filho, Paulo Noronha [UNESP]; Cavalli, Vanessa; Basting, Roberta Tarkany (Elsevier, 2023)
Background: The purpose of this study was: 1) to analyze the physical-chemical properties of hydrogen peroxide (HP) agents at 7.5% (HP7) and 35% (HP35), and the association with or without TiO2 nanotubes; 2) to evaluate dental bleaching effectiveness by using HP7 and HP35 together with or without TiO2 nanotubes, and applied with or without violet LED (VL). Methodology: 80 bovine incisors were treated according to groups (n = 10): HP35; HP35 + VL; HP35T (HP35 + TiO2); HP35T + VL; HP7; HP7 + VL; HP7T (HP7 + TiO2); HP7T + VL. Bleaching effectiveness was measured at 4 time points according to the Vita Classical, CIEL*a*b*, CIEDE2000, and WID parameters. HP35, HP35T, HP7, and HP7T were evaluated for mass change, pH, mean particle size (P), polydispersity (PDI), and zeta potential (ZP), over 6 months of storage. Results: The pH of HP35 thickener was higher when associated to TiO2. At baseline, both of the bleaching gels containing TiO2 had lower P, PDI, and PZ (p < 0.05). All groups showed a significant decrease in Vita Classical color scores (p = 0.0037). There was a higher L* value, and lower b* values for HP7 when associated to VL after the 3rd session. (p < 0.05). HP35T showed higher color change (ΔEab, ΔE00), and lower a* value in the presence of VL (p < 0.05). ΔWID presented lower values for both gels, when TiO2 was incorporated (p ≤ 0.05). Conclusion: The incorporation of TiO2 to the bleaching gel showed good stability with minimal variations in physical-chemical properties. The color change in HP35 was more effective than in HP7, but the VL boosted the bleaching effectiveness of HP7, whereas TiO2 did not increase bleaching effectiveness.
Keywords: Bleaching; Hydrogen peroxide; Titanium dioxide; Violet LED